Nonlinear dynamics of femtosecond laser interaction with the central nervous system in zebrafish - Jun, Soyeon; Herbst, Andreas; Scheffter, Kilian; John, Nora; Kolb, Julia; Wehner, Daniel; Fattahi, Hanieh (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2025)
Understanding the photodamage processes driven by the complex nonlinear interactions of femtosecond laser pulses within the second tissue transparency window is pivotal for developing novel label-free microscopy techniques. In this research, we identify two distinct cavitation mechanisms produced by 1030 nm femtosecond pulses in the zebrafish central nervous system. The damage remains highly localized for irradiation at lower laser repetition rates, resulting from plasma-induced ablation and localized heating. In contrast, higher laser repetition rates lead to more extensive damage mediated by plasma-induced photochemical reactions. We also investigate how fluorescence labels, involving both linear and nonlinear absorption pathways, influence the dynamics of the photodamage. To confirm our findings, we analyzed cell death and tissue responses to laser-induced injury, including the activation of fibroblasts and the recruitment of immune cells.
CRIS-Team Scopus Importer:2025-05-16
Keywords: central nervous system; deep-tissue imaging; femtosecond pulses; light tissue interaction; photodamage; photothermal damage; phototoxicity; reactive oxygen species; zebrafish